18. Quality assurance in proton magnetic resonance spectroscopy: Final results of an intercomparison of 18 clinical scanner systems. (December 2018) - Sghedoni, R.; Coniglio, A.; Mazzoni, L.N.; Belli, G.; Tarducci, R.; Busoni, S.; Esposito, M.; Nocetti, L.; Ciccarone, A.; Altabella, L.; Levrero, F.; Fedeli, L.; et al.
Abstract : Purpose: Quality assurance in advanced and quantitative magnetic resonance techniques is strongly recommended[1–3] . The aim of this study was to propose and validate across various clinical scanner systems a straightforward quality assurance procedure for proton Magnetic Resonance Spectroscopy (MRS). Methods: Eighteen clinical 1.5 T and 3 T scanners for MRS were enrolled in the study. The protocol included 3 sets of single voxel PRESS acquisitions without water signal suppression, repeated 4/5 times within approximately 2 months and performed using a standard water phantom supplied to all centres. Water peak linewidth (LW), water peak area (AP) and phantom T2 were estimated. Results: LW values ranged from 0.4 Hz to 1.6 Hz, with 3 T and 1.5 T scanner systems showing similar performances. Coefficient of variation (CV) of LW values for repeated measurements were lower than 35% (except for only 3 scanners). AP showed significant (p < 0.05) linear correlation with voxel volume (r > 0.99 and 0.95 for 1.5 T and 3 T scanner systems, respectively). CV of AP for different spatial positions was less than 25%, and no relevant difference was observed between 3 T and 1.5 T scanners. Mean phantom T2 value and CV for repeated measurements were 1147 ms and 4%, respectively, for 1.5 T scanners, and 1010 ms and 9%, respectively, for 3 T scanners. Conclusions: We proposed a straightforward multiparametric and not time consuming quality control protocol for MRS, which can be included in routine quality assurance procedures. The protocol has been validated and proven to be feasible in a multicentre intercomparison study of 18 clinical 1.5 T and 3 T scanner systems.